Laumė’s broom or the Image of the Mistletoe in Traditional Lithuanian Culture - Macijauskaitė-Bonda, Jurgita (Tautosakos darbai, 2016)
Mistletoe (Lith. amalas) is a widespread parasitic plant that is mentioned in various beliefs, myths and other traditional narratives, and is used in rituals, different magic practices and folk medicine. In Lithuania, only one of its species, Viscum album, is known. Even though the mistletoe played an important role in other European cultures, for instance, Druidic and Norse mythologies, the data about its place in the archaic Lithuanian worldview is quite fragmentary. Most probably it is caused by the climatic conditions with relatively frosty winters that limited the spread of the plant in the country.The aim of this article is to collect and systemise the data regarding the mistletoe, and taking into consideration folklore, linguistic and ethnographic material, reveal its image in the traditional Lithuanian culture. While analysing the data, it was noticed that the Lithuanian word amalas and the other names defining the mistletoe, as for instance laumės šluota, i.e. the broom of laumė (a fairy in Lithuanian folklore) are polysemantic and can be used to name not only the evergreen scrub growing on the trees but also certain dense mases of shoots growing from a single point on birch trees, that are caused by the parasitic fungus Taphrina betulina and resemble a broom or a bird’s nest (in English, the latter are called witch’s brooms). For this reason, the research field was expanded to include not only the mistletoe but also the witch’s broom. It is also important to mention that in the ancient Lithuanian worldview both plants quite often were treated in similar ways. The article first discusses the names of the plants, then etiological narratives about the occurrence of the mistletoe and the witch’s broom are analysed, and last their image in folklore, folk beliefs and customs is revealed. The methodology of the research presented in this article consists of analytical descriptive and comparative analysis, Lithuanian data is compared with analogous examples from other nations’ folklore, customs, beliefs, lexical and phraseological facts.The research revealed that even though data regarding the image of the mistletoe is not very rich, it shows that Lithuanians knew this plant and attributed to it magical powers. In the literary Lithuanian language and its dialects, the mistletoe, Lith. amalas is also called amuolas, tirkšlys, tiršlys, prilypas, laumšluotė, laumės / raganos / raganės / velnio šluota (fairy’s / witch’s / devil’s broom), but the idiomatic expression laumė’s or witch’s broom refers not only to the mistletoe but also to the ball-shaped bundle of twigs that resembles a mistletoe (called witch’s broom in English). Based on the results obtained, it can be claimed that both the image of the mistletoe and that of the witch’s broom from the mythical symbolic perspective in certain cases are identical; both plants are related to mythical beings, mythical space between the earth and the sky, and are attributed analogous protective powers. In the ancient Lithuanian worldview, as an evergreen the mistletoe was also given the symbolic meaning of vegetation, vitality and fertility. In the Advent-Christmas period song accompanying the game Grįskime mergos ievaro tiltą (“Girls, Let’s Make a Ievaras Bridge”) the mistletoe mentioned as a material for the construction of the symbolic bridge represents vitality and together with the mythologeme of the other mythical plant ievaras transmits the symbolic meaning of the bridge that must be crossed by young matured people during the sacred period.
Keywords: -